Ahmad b. Hanbal's method in hadith and transmitters/rijal criticism - Kutluay, İbrahim (SILA SCIENCE, 2011)
No doubt that knowledge of hadith and its ancillary sciences are the exclusive characteristic of Muslim civilization. In this respect, Ahmad b. Hanbal (d. 241/855) is the celeberated hadith scholar and the champion of the Surma and the senior figure of community. He is also one of the best scholars on hadith science, particularly in fiqh al- hadith, hadith criticism and al-jarh and ta 'dil/ credit and discredit. He embraced some principles to evaluate the transmitting and transmitters of hadith. Thus, he referred to these rules and their applications, though not explicitly, in his book ma'rifa al-Rijal which was compiled by his son Abdullah after his demise. Most of hadith and law experts unanimously agree on stipulating that the person whose transmission may be adduced as a proof be upright (ad]) and accurate (dabit) in what he relates. Specifically, he must be Muslim; adult; of sound mind; fret of tendencies toward impiety and defects of character; alert; careful; retentive, if he transmits from memory; and accurate in handling his text, if transmits from it. So, in this paper I will try to determine which rules Ahmad b. Hanbal established for hadith criticism and how extend he applied them his masterpiece al-Musnad. I will also study the method of Ahmad b. Hanbal's in hadith criticism. In so doing, I will deal with first how the science of jarh and ta'dil/ appeared, the main principles of the imams in jarh and ta 'dil and in which subjects in hadith Ahmad b. Hanbal has tolerance.
Keywords: Ahmad b. Hanbal; Hadith Criticism; Isnad; 'Ilal; al-Musnad